Performance analysis and mathematical modelling of banana slices in a heat pump drying system - Tunckal, Cuneyt; Doymaz, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
In this study, banana slices were dried at different temperatures in a closed-loop heat pump drying system. As the temperature and the slice thickness increased, the drying time also increased. Midilli & Kucuk model was found to be the best model to explain the experimental data. The effective moisture diffusivity ranged from 1.12 x 10(-10) to 1.64 x 10(-10) m(2)/s. The dependence of moisture diffusivity on temperature was described by an Arrhenius-type equation and the activation energy was found to be -51.45 kJ/mol. The highest mean specific moisture extraction ratio (SMER) and coefficient of performance (COP) of HPD system were obtained as 0.212 kg/kWh and 3.059, respectively, at the highest drying air temperature. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Activation energy; Banana slices; Effective moisture diffusivity; Heat pump drying system; Mathematical modelling; EXERGOECONOMIC EVALUATION; TOMATO SLICES; KINETICS; TEMPERATURE; DRYER; LAYER; SIMULATION; SHRINKAGE; PART; Science & Technology - Other Topics; Energy & Fuels